From Endoscopic Detorsion to Sigmoid Colectomy—The Art of Managing Patients with Sigmoid Volvulus: A Survey of the Members of the American Society of Colon and Rectal Surgeons. Issue 9 (September 2018) - Garfinkle, Richard; Morin, Nancy; Ghitulescu, Gabriela; Vasilevsky, Carol-Ann; Boutros, Marylise
This study queried American Society of Colon and Rectal Surgeons members for management of sigmoid volvulus and aimed to determine whether surgeon experience impacts decision-making. American Society of Colon and Rectal Surgeons members received a 16-item survey in March, 2017. Items included endoscopic detorsion technique and colonic decompression, preoperative dietary considerations, surgical approach, and respondents' demographics. Respondents were separated into low experience (LE; ≤10 years in practice) and high experience (HE; >10 years in practice). Of 1996 survey recipients, 10 per cent (197) responded; 124 were HE and 73 were LE. Most were fellowship-trained (93.8%) and primarily in colorectal surgery practice (74.6%), however only 27.4 per cent managed >20 sigmoid volvulus cases as attendings. Fifty-two per cent use rectal tubes for continued colonic decompression after successful endoscopic detorsion; 81.2 per cent would perform sigmoid colectomy on the index admission after successful detorsion, but within a variable timeframe (one to seven days postdetorsion) and with variable dietary restrictions in the interval period; 49.7 per cent would perform a laparoscopic colectomy and 68.3 per cent would perform a stapled colorectal anastomosis. LE surgeons reported a higher proportion of gastrointestinal-performed endoscopic detorsions (P = 0.015), were more likely allow regular diet in the interval period (P = 0.031), and were more inclined to use laparoscopy (P = 0.008), versus HE surgeons. There remains controversy among many of the components in the management of sigmoid volvulus after successful endoscopic detorsion.